2008
DOI: 10.1097/01.ncn.0000304781.27070.a7
|View full text |Cite
|
Sign up to set email alerts
|

Use of the HESI Admission Assessment to Predict Student Success

Abstract: This study examined the value of the HESI Admission Assessment in predicting student success. Associate degree (N = 68) and baccalaureate (N = 69) nursing students took the HESI Admission Assessment after acceptance into the nursing programs for the purpose of identifying their academic weaknesses and focusing their remediation efforts. Findings indicated that the HESI Admission Assessment was a valid predictor of students' academic ability to succeed in the nursing programs. In the associate degree nursing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…Scores range from 0-100 % on all HA 2 component exams. Reliability coefficients have been reported at .99 for each of the HA 2 exams used in this study (Murray, Merriman, & Adamson, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…Scores range from 0-100 % on all HA 2 component exams. Reliability coefficients have been reported at .99 for each of the HA 2 exams used in this study (Murray, Merriman, & Adamson, 2008).…”
Section: Methodsmentioning
confidence: 99%
“…7 The HESI Admission Assessment taken by new nursing students was found to be almost 90% predictive of course grades in the associate degree program and 50% for bachelor degree-seeking students. 8 Harding 9 found those students who were not successful had a score below 800 on the mid-curricular HESI exam. This, in turn, is a good predictor of at-risk students early in their curricular progression.…”
Section: Introductionmentioning
confidence: 99%
“…Only a few studies have used admissions tests to predict the success of completion of a BSN programme. Murray et al . found that admissions tests scores, such as math, English, basic sciences and comprehensive reading, were positively correlated with the course grades in the nursing programme.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that the pre-nursing GPA and prerequisite nursing courses were predictive of successful completion of BSN programmes. 5,7,8 Only a few studies 9 have used admissions tests to predict the success of completion of a BSN programme. Murray et al 9 found that admissions tests scores, such as math, English, basic sciences and comprehensive reading, were positively correlated with the course grades in the nursing programme.…”
Section: Introductionmentioning
confidence: 99%